Mandatory CSR disclosure regulation and stock price synchronicity: evidence from a quasi-natural experiment - Chuang Wu (Humanities & Social Sciences Communications)
Abstract Using the mandatory CSR disclosure policy enacted in China as a quasi-natural experiment, this study provides causal evidence that mandatory CSR disclosure regulation increases stock price synchronicity. Drawing upon signaling theory and behavioral finance perspective, I argue that mandatory CSR disclosure regulation as a market level signal may affect investors’ category-learning behavior, which can further have a positive impact on stock price synchronicity. I further show that this positive impact can be attenuated when firms are followed by more analysts, when more following analysts are affiliated with large brokerage firms, and when firms have better corporate governance. This study not only provides new evidence that mandatory CSR disclosure regulation can positively affect stock price synchronicity but also suggests that analysts’ capabilities to extract and understand CSR information and better corporate governance can alleviate such an effect.